Waste-to-Wealth (Taylor & Francis, 2024)
This book covers state-of-the-art resource recovery technologies from the different components of solid waste, such as plastics, e-waste, fly ash, sewage sludge, slag and their real applications. Furthermore, it explains various management strategies for agricultural waste, including the generation of bioenergy from agri-crop residue. It also highlights the recent technologies used in the management of industrial waste, their implementation at a large scale and the treatment of industrial effluent with the rationale synthetic approach, hybrid advanced oxidation process and bio-methanation. Features: Provides a technical interpretation for creating wealth from waste by the experts in the research domain. Covers various aspects of waste management, current resource recovery and recycling trends. Presents a unique combination of municipal, agricultural and industrial waste management towards achieving a resilient smart city. Imparts knowledge of policies and regulations in different countries and their impacts on waste management. Illustrates various technologies for waste processing through case studies. This book is aimed at researchers and policymakers in environmental engineering, waste management and clean energy. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.